Meningkatkan Keterampilan Bahasa pada Anak Usia 3 Tahun Melalui Media Flashcard di Desa Pelabuhan Dalam - Padila Choirunisa; Dwi hurriyati; Asmanita (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Early childhood is a child in the period from birth to six years of age who requires growth and development stimulation for the process of readiness to enter the world of education. Early Childhood Education is essentially education that is organized with the aim of encouraging and facilitating the growth and development of children's abilities. The abilities that need to be developed focus on children's language skills. Language is an expression that contains the intention of conveying something to another person. using the learning method with flashcard picture card media is one media that can be considered and used to improve language development for young children. The result of this service is that there is an increase in language skills in children after learning actions using flashcard media. There is an increase in the vocabulary mastered by children.